2023
DOI: 10.1021/acsami.3c03113
|View full text |Cite
|
Sign up to set email alerts
|

Fabric-like Electrospun PVAc–Graphene Nanofiber Webs as Wearable and Degradable Piezocapacitive Sensors

Abstract: Flexible piezocapacitive sensors utilizing nanomaterial−polymer composite-based nanofibrous membranes offer an attractive alternative to more traditional piezoelectric and piezoresistive wearable sensors owing to their ultralow powered nature, fast response, low hysteresis, and insensitivity to temperature change. In this work, we propose a facile method of fabricating electrospun graphene-dispersed PVAc nanofibrous membrane-based piezocapacitive sensors for applications in IoT-enabled wearables and human phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Recently, Sengupta et al reported graphene-polyvinyl acetate (PVAc) nanofiber-based degradable piezocapacitive sensors for human physiological parameters monitoring. [102,113] Similar to the work of Sharma et al, [19] this work fundamentally investigated the effect of 2D nanomaterial filler (graphene) addition on the dielectric constant of PVAc polymer. The sensor reported in the work featured a nanofibrous membrane sandwiched between two layers of circular silver-plated nylon fabric electrodes and optically clear adhesive plate seals for complete encapsulation as shown schematically in Figure 8l.…”
Section: Fibrous Structure-based Sensorsmentioning
confidence: 90%
See 3 more Smart Citations
“…Recently, Sengupta et al reported graphene-polyvinyl acetate (PVAc) nanofiber-based degradable piezocapacitive sensors for human physiological parameters monitoring. [102,113] Similar to the work of Sharma et al, [19] this work fundamentally investigated the effect of 2D nanomaterial filler (graphene) addition on the dielectric constant of PVAc polymer. The sensor reported in the work featured a nanofibrous membrane sandwiched between two layers of circular silver-plated nylon fabric electrodes and optically clear adhesive plate seals for complete encapsulation as shown schematically in Figure 8l.…”
Section: Fibrous Structure-based Sensorsmentioning
confidence: 90%
“…Plot showing the sensor responses from the bilateral hamstring, scapula, and gluteal muscle region of a test subject while being seated upright. [102] Reproduced under the terms of the Creative Commons CC BY 4.0 license. [102] Copyright 2023, the Authors, published by ACS.…”
Section: Fibrous Structure-based Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…are some of the widely used forms of dressing materials. Sponges with appropriate gas exchange, acceptable mechanical properties, favorable interconnected pore size, and a noticeable capability of fluid absorption and holding are widely used as a suitable wound dressing. , Additionally, the nanofibrous electrospun membrane is also extensively utilized as a functional structure for wound treatment as it provides a high surface area, mimics the extracellular matrix (ECM), has outstanding mechanical properties, and has exceptional and adaptable chemical, physical, and biological properties. The main drawback of single-layer wound dressings is that they cannot imitate the hierarchical structure of the skin and provide all clinical needs. , Sponge matrices are preferable to thin membranes for healing full-thickness wounds, but on the other hand, nanofibrous membranes have an ECM-like structure and are more suitable for cell adhesion and proliferation. Therefore, by creating a nanofibrous layer under the sponge matrix, the advantages of both structures can be achieved .…”
Section: Introductionmentioning
confidence: 99%